(untitled) - Horngren, Charles T. (Englewood Cliffs, N.J., 1972)
Appropriate for a one- or two-term Introductory/Intermediate level course in cost/management accounting. Also suitable for MBA level courses.This market leader continues the basic theme of all previous editions: "different costs for different purposes."Cost Accounting, Third Canadian Edition, goes beyond cost accounting procedures and also stresses concepts, analysis and the use of cost accounting as a management tool.
Keywords: Cost accounting,Kế toán giá thành